PENTINGNYA PENDIDIKAN KEWARGANEGARAAN DALAM PEMBENTUKAN MORAL GENERASI MILENIAL DI ERA GLOBALISASI - Intan Permata Sari; Irma Wati Pasaribu; Muhammad Zahien Akbar AS; Berlian Cikka Octanelsha (CV. ADIBA AISHA AMIRA, 2024)
The moral crisis currently hitting the millennial era has raised deep concerns about the moral values of today's society. The ethical crisis in the millennial era is becoming an increasingly deep and complex problem. Various factors, such as the influence of globalization, technological progress, and social change, have shaped the context of individual behavior and weakened basic moral values. In this context, this review examines the importance of citizenship education as the main solution for forming individual character and social ethics in the millennium era. This study discusses the concept of citizenship education, the role of educational institutions and the challenges faced in realizing civic values in education. The research results highlight the importance of citizenship education in overcoming the current moral crisis and emphasize the need for cooperation between government, educational institutions and society to achieve this goal.